2021
DOI: 10.3390/w13243543
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Net Anthropogenic N Inputs and Export Fluxes in the Megacity of Chengdu, China

Abstract: Anthropogenic N inputs have become progressively more problematic and have profoundly affected the water quality in megacities throughout China. Thus, to design and implement appropriate megalopolis watershed management, it is important to understand the relationship between N inputs and exports and to identify the N pollution sources. To that end, in this work, the net anthropogenic N inputs (NANI) in Chengdu City were estimated based on statistical data collected between 1970 and 2019. N input fluxes and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The assessment of the different forms of N is essential to a correct interpretation of N cycling (Ding et al, 2021; Fadhullah et al, 2020; X.‐L. Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The assessment of the different forms of N is essential to a correct interpretation of N cycling (Ding et al, 2021; Fadhullah et al, 2020; X.‐L. Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the DO concentration (mean 7.58 ± 0.93 mg/L) measured in the main stream during the dry season was not ideal for denitrification (<1 mg O 2 /L; Soto et al, 2019). It is suggested that these results reflect groundwater input with significant denitrification characteristics (Ding et al, 2021). Therefore, it is reasonable to ignore denitrification, and assume that mixing with atmospheric NO 3 − was the dominant factor for the high 18 O-NO 3 − obtained during the rainy season (Ding et al, 2014).…”
Section: The Key Nitrate Conversion Processmentioning
confidence: 95%
See 3 more Smart Citations